Assessing traffic-related environmental impacts based on different traffic monitoring applications - Teixeira, João (2019)
The objective of this study is to propose a methodological approach to assess the capability of different traffic monitoring applications to estimate emissions generated by road traffic. Global Navigation Satellite Systems and traffic data were collected from different roadways in Portugal and Spain. Emissions were estimated through the Vehicle Specific Power concept, and then, data mining tools were explored to reveal patterns hidden on large amount of data (154 000 sec). Finally, the best relationships between traffic variables and emissions are evaluated. Results show a prediction for CO2 emissions of 99% and 98% to NOX.